The prevalence of retinopathy in diabetes mellitus and associated risk factors: a community-based cross sectional study in peri urban area - Gupta, Sanjeev K.; Sharma, Anshuman; Agarwal, Sanjay; Gupta, Sanjay; Sarouthia, Shalini (International Journal Of Community Medicine And Public Health, 2018)
Background: Visual impairment i.e. diabetic retinopathy is the one of most common manifestation of diabetes mellitus. Globally it is becoming an increasing public health problem especially in the developing countries because of increase in number of diabetic patients. Methods: A cross sectional study was conducted in the vicinity of Urban Heath and Training Centre (UHTC), Peoples University, Bhopal over a period of 6 months through screening in camps held, which included a total of 840 participants (aged ≥25 years) by following simple random procedure and in those who had newly diagnosed or long standing diabetes were referred to ophthalmologist for further evaluation. Retinopathy was determined by ophthalmoscopy and fundus photography. Anthropometric measurements (BMI), glycosylated haemoglobin were also evaluated among the confirmed diabetic patients in the study. Results: An increased prevalence of diabetes (5.95%) and retinopathy (28%) (95% CI 11.2-32.0) was found. In all age groups prevalence of bilateral blindness, bilateral low vision, unilateral blindness and unilateral low vision were respectively 2%, 28%, 0%, 70%. Independent risk indicators for the occurrence of diabetes such as age, BMI, HbA1c, were found significant for the occurrence of retinopathy in the study population. Conclusions: Visual impairment due to diabetic retinopathy remains an important public health problem in people with diabetes so timely interventions are required to resolve this major issue.